Effect of Chronic Periodontitis on Oxidative Status in Patients With Rheumatoid Arthritis. Issue 6 (1st June 2013) - Sezer, Ufuk; Erciyas, Kamile; Üstün, Kemal; Pehlivan, Yavuz; Ziya Şenyurt, Süleyman; Aksoy, Nurten; Tarakçıoğlu, Mehmet; Taysı, Seyithan; Onat, Ahmet Mesut
Abstract : Background: Rheumatoid arthritis (RA) and chronic periodontitis (CP) are the most common chronic inflammatory diseases and have remarkable similar pathologies. The aim of this study is to investigate the impact of periodontal status on oxidative stress in patients with RA by evaluating serum oxidative parameters and prolidase levels. Methods: For this cross‐sectional comparative study, the following four groups were composed of 20 individuals each (80 individuals total): 1) RA with CP (RA‐CP group); 2) RA but periodontally healthy (RA‐C group); 3) systemically healthy with CP (CP group); and 4) systemically and periodontally healthy (C group). Demographic, periodontal, rheumatological, and serum oxidative parameters as determined by serum total antioxidant status, total oxidant status, oxidative stress index (OSI), lipid hydroperoxide levels, paraoxonase, arylesterase, and ceruloplasmin activity, prolidase level, and total sulfhydryl groups were evaluated. Results: The OSI values of the RA‐CP group were statistically significantly higher than those of the C group ( P <0.05). The prolidase levels of the RA‐C, RA‐CP groups and the CP group were statistically higher than those of the C group ( P = 0.001, P = 0.007, and P = 0.001, respectively). Conclusions: Although CP and RA each increase oxidative stress, in a small sample size these effects are only significant when both CP and RA are combined relative to neither exposure. In addition, increased prolidase levels in patients with RA and CP may be related to increased oxidative tissue damage.